2016
DOI: 10.1167/iovs.16-19862
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profile in Conjunctival Melanoma

Abstract: PURPOSE. Conjunctival melanoma (CM) is a rare disease associated with considerable mortality. As opposed to cutaneous melanoma, the epigenetic mechanisms involved in the development of CM and other mucosal melanomas (MMs) are unclear. The purpose of this study was to identify tumor-specific and prognostic microRNA (miRNA) in CM and to compare the miRNA profile with that of MM.METHODS. Using microarray analysis (Affymetrix) we determined the miRNA expression profile in 40 CMs compared with 7 normal conjunctival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Moreover, we detected several differentially expressed miRNAs that have not been reported previously (Table S2). [22][23][24][25][26]. The expression trends of these miRNAs correlated well between human melanoma and COM.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, we detected several differentially expressed miRNAs that have not been reported previously (Table S2). [22][23][24][25][26]. The expression trends of these miRNAs correlated well between human melanoma and COM.…”
Section: Discussionmentioning
confidence: 73%
“…A literature search on miR-3687 retrieved only a few articles related to malignant neoplasia. One study has referred to invasive ability and poor prognosis of oesophageal cancer, another to increasing local recurrence of conjunctival melanoma and a third to telomerase activity of a breast cancer cell line (30,33,34). The present study was the first to investigate both miR-3687 as a differentially expressed miRNA in BSCCE and its putative target genes in oesophageal carcinoma.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, cases with high expression of miR-3687 resemble BSCCE with aggressive biological features, resulting in poor prognosis. It was reported that miR-3687 was highly expressed in conjunctival melanoma; moreover, miR-3687 upregulation was also related to high risk of local recurrence (33). However, no study to date has assessed the impact of miR-3687 in oesophageal cancer.…”
Section: Discussionmentioning
confidence: 99%